Inovasi Sistem Electronic Nose untuk Monitoring Kualitas Oli dan Deteksi Dini Kerusakan Ring Piston pada Mesin Kapal Nelayan (Studi Kasus: Kampung Nelayan Desa Kronjo) - Ikhwanuddin Ikhwanuddin; M. Anang Jatmiko; A. Nur Fajri Irwan; Ferro Hidayah; Juliaster Marbun (Yayasan Literasi Sains Indonesia, 2025)
Electronic Nose system to optimize fishing vessel engine maintenance through in situ oil quality monitoring. This system integrates four gas sensors (TGS 813, TGS 822, TGS 2600, TGS 2602) with a DC pump and Arduino Uno, enabling early detection of piston ring damage without disassembling the engine. It detects volatile compounds in the oil, such as heavy metals and acidic substances caused by piston friction, using the iontophoresis method.Sensor readings for normal piston rings are: TGS2600 (410–600 mV), TGS2602 (200–210 mV), TGS813 (55–60 mV), TGS822 (70–110 mV); for worn rings: TGS2600 (540–730 mV), TGS2602 (330–350 mV), TGS813 (100–107 mV), TGS822 (90–150 mV); and for scratched rings: TGS2600 (480–690 mV), TGS2602 (220–245 mV), TGS813 (80–90 mV), TGS822 (100–200 mV).With real-time damage detection, this technology reduces repair time, cuts operational costs, and extends engine life. Additionally, it supports lower carbon emissions and oil waste, contributing to environmental sustainability. The adoption of Nautical Guardian is expected to improve the productivity and income of fishermen, particularly in Kronjo Fishing Village, Tangerang City